Снижение инкрустации дистиллера путем снятия пересыщения по сульфату в реакторе-смесителе отделения дистилляции - Филоненко, Денис Владимирович; Райко, Валентина Федоровна; Шестопалов, Алексей Валерьевич (НТУ "ХПИ", 2014)
В статье рассмотрены причины сульфатной инкрустации отделения дистилляции содового производства. Исследованы пути снижения кристаллизации ангидрита на поверхности дистиллера и трубопроводов. Установлено, что с повышением температуры и концентрации ангидритной затравки скорость кристаллизации сульфата кальция возрастает. Отгонка части аммиака и воды непосредственно в смесителе на барботажных тарелках также способствует кристаллизации ангидрита и ускоряет процесс снятия пересыщения по гипсу.

The reasons of sulfate encrustation of departmentdistillation of ash production are considered in the article. The ways of decline of crystallization of anhydrite are investigational on-the-spot distiller and pipelines. Research of continuous supersaturation relieving on CaSO₄ in distiller retention time 5-120 minutes. Experiments showed that use of vapour-liquid injector as a primary mixer and heater of reagents, before their serve in an industrial reactor-mixer executing the function of liquidator supersaturation relieving on CaSO₄. It is set that with increasing temperature and concentration of anhydrite inoculating speed of crystallization of calcium sulfate increases. Distillation part of ammonia and water directly in a mixer on bubble-type piattis is also instrumental in crystallization of anhydrite and accelerates a process continuous supersaturation relieving on CaSO₄. Exposed, that the ways of improvement of construction of reactor-mixer are analysed for the decline of anhydrite concentration.
Decline of encrustation of distiller by the continuous supersaturation relieving on sulfate in the reactor-mixer of distillation department
Keywords: инкрустация аппаратуры; производство соды; дистиллер; кристаллизация ангидрита; encrustation of apparatus; reactor-mixer; ash production; distiller; crystallization of anhydrite